Assessment of Malaysian Laterite Aggregate in Concrete - Khairunisa, Muthusamy; Norul Wahida, Kamaruzaman (IJENS, 2012)
Integration of new material as a partial coarse aggregate replacement in local concrete production would be able to reduce the high dependency of concrete manufacturer on granite aggregate supply that may lead to ecological imbalance when this natural material is used excessively. This paper presents the assessment on the characteristic of Malaysian laterite aggregate obtained from several locations before discussing further on the influences of this local material towards engineering properties of normal concrete. Concrete mixes containing 0%, 10%, 20%, 30%, 40% and 50% laterite aggregate replacement level were cast before subjected to water curing for 7, 14, 28 and 60 days. Workability test, compressive strength test, flexural strength and modulus of elasticity were conducted in accordance to the existing standard. Results show that replacement of appropriate laterite aggregate content able to produce workable concrete with satisfactory strength. Addition of 10% replacement laterite aggregate able to produce mix with comparable strength to plain concrete. The targeted strength still can be achieved with addition of 30% replacement laterite aggregate.